Use of dietary supplements containing soy isoflavones and breast cancer risk among women aged >50 y: a prospective study. Issue 3 (4th March 2019) - Touillaud, Marina; Gelot, Amandine; Mesrine, Sylvie; Bennetau-Pelissero, Catherine; Clavel-Chapelon, Françoise; Arveux, Patrick; Bonnet, Fabrice; Gunter, Marc; Boutron-Ruault, Marie-Christine; Fournier, Agnès
ABSTRACT: Background: Soy-based dietary supplements have been promoted as natural alternatives to menopausal hormone therapy, but their potential effect on breast cancer development is controversial. Objectives: We examined the relation between the consumption of soy supplements and the risk of breast cancer, overall and by tumor hormone receptor status, among women aged >50 y. Methods: In total, 76, 442 women from the Etude Epidemiologique aupres de Femmes de la Mutuelle Generale de l'Education Nationale (E3N) cohort, born between 1925 and 1950, were followed from 2000 to 2011 (11.2 y on average, starting at a mean age of 59.5 y; 3608 incident breast cancers), with soy supplement use assessed every 2–3 y. HRs of breast cancer were estimated with the use of multivariable Cox models. Results: Compared with never using soy supplements, the HRs associated with current use of soy supplements were 0.92 (95% CI: 0.76, 1.11) for all, 0.78 (95% CI: 0.60, 0.99) for estrogen receptor (ER)–positive, and 2.01 (95% CI: 1.41, 2.86) for ER-negative breast cancers. There was no association between past use of soy supplements and breast cancer. HRs for current use were 1.36 (95% CI: 0.95, 1.93) and 0.82 (95% CI: 0.65, 1.02) among women with and without a family history of breast cancer, respectively ( P -interaction = 0.03) and 1.06 (95% CI: 0.87, 1.30) ≥5 y after menopause compared with 0.50 (95% CI: 0.31, 0.81) in premenopause or ≤5 y postmenopause ( P -interaction = 0.04). Conclusions: In this cohort of women aged >50 y, we report opposing associations of soy supplements with ER-positive and ER-negative breast cancer risk. Our results also caution against the use of these supplements in women with a family history of breast cancer. Whether the risk profile of soy supplements could be more favorable among premenopausal or recently postmenopausal women deserves further investigation.